Proton conductivity of Nafion-azolebisphosphonates membranes for PEM fuel cells - Teixeira, Fatima (2018)
ABSTRACT: Energy systems with cleaner and sustainable sources are crucial challenges of the 21st century to deal with the environmental threat of global warming and the declining reserves of fossil fuels. Fuel cells are electrochemical devices that convert the chemical energy stored in a fuel directly into electrical energy, providing electrical energy with high efficiency and low environmental impact. Among them, proton exchange membrane fuel cells (PEMFCs) are considered promising power sources, due to their high power density and high power-to-weight ratio but their performance depends crucially on their proton exchange membranes. Usually, these membranes are made of organic polymers containing acidic functionalities (ex. Nafion®), which proton transport properties strongly depend on their water content and, consequently, limit their operation temperatures up to 90ºC. Preliminary studies have demonstrated that incorporation of aryl-bisphosphonic acids into Nafion, by casting, results in an enhancement of the proton conductivity of the membrane. The aim of this work was the preparation of new Nafion membranes doped with azolebisphosphonates derivatives, which could act as a source of protons and also function as proton acceptors, facilitating the intermolecular transmission of protons through the membrane.